ТЕХНОЛОГИИ ПРОИЗВОДСТВА ФЕРРОНИКЕЛЯ ИЗ РУД РАЗЛИЧНЫХ МЕСТОРОЖДЕНИЙ (Modern Problems of Metallurgy, 2020)
The results of the comparative analysis of ferronickel production indicators in terms Pobuzhsky ferro-nickel plant using domestic raw materials (Kapitanovskogo) and abroad (New Caledonia, Indonesia, Guatemala) deposits. Introduction of innovation and investment activities: pre-drying of ore; getting cinder in tubular rotary kilns using coal injection (PCI); reconstruction of furnace number 1, it will improve the actual power up to 42 MW; development of ferronickel smelting roughing technology in this furnace to a lack of a reducing agent, and others. have provided an opportunity to significantly reduce production costs and improve production efficiency. The method of X-ray microanalysis (EPMA) studied the distribution of trace elements in the samples of crude ferronickel and mastered traditional techniques. It is shown that the sulfur is present as manganese sulphide (MnS), and its content is 2 times higher than in the conventional alloy.
Keywords: nickel raw materials, ore-thermal furnace, sulfur, refining, melting soda, EPMA, sulfides